Hypercatecholaminaemia in stress urinary incontinence and its pathogenetic treatment perspectives: an experimental non-randomised study - A. Kh. Kade; D. N. Kazanchi; P. P. Polyakov; S. A. Zanin; P. A. Gavrikova; Z. O. Katani; K. M. Chernysh (Кубанский научный медицинский вестник, 2022)
Background. Urinary incontinence is associated with chronic psycho-emotional stress. Stress management should be part of a comprehensive treatment for urinary incontinence.Objectives. An assessment of hypercatecholaminaemia severity and dynamics in repeated courses of TES therapy for stress urinary incontinence.Methods. A total of 100 stress urinary incontinence patients were divided between a comparison and two main cohorts. Main cohort 1 (n = 30) received a modern standard treatment in combination with TES therapy. TES therapy was performed in three courses (1 session per day for 7 days): course 1 on admission, course 2 in 3 months after course 1, course 3 in 6 months after course 1. Main cohort 2 (n = 40) received a modern standard treatment in combination with two short courses of TES-therapy (2 sessions per day for 7 days): course 1 on admission, course 2 in 6 months after course 1. The comparison cohort (n = 30) only had standard treatment. Catecholamine concentrations were assessed over time in each cohort.Results. Catecholamine concentrations were >2 times higher before treatment in all cohorts vs. healthy volunteers. The comparison cohort revealed adrenaline and noradrenaline concentrations 71.2% (p < 0.05) and 84.0% (p < 0.05) higher vs. healthy volunteers, respectively, by month 6 of the trial. Main cohort 1 had the concentrations of adrenaline and noradrenaline 2.1 (p < 0.05) and 1.5 (p < 0.05) times higher, respectively, vs. healthy volunteers. Main cohort 2 showed an adrenaline concentration 12.5% (p < 0.05) and noradrenaline — 2.4% higher (p = 0.15) vs. healthy volunteers.Conclusion. TES therapy affects urinary incontinence hypercatecholaminaemia, demonstrating a favourable homeostatic impact on neuroimmunoendocrine regulation.